6th Hybrid and Electric Vehicles Conference (HEVC 2016) 2016
DOI: 10.1049/cp.2016.0987
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Direct Current Street Lighting & Integrated Electric Vehicle Charging Points

Abstract: This version is available at https://strathprints.strath.ac.uk/58254/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…With respect to EV charging, 'fast' off-board DC chargers are believed to offer the most practical public charging system based on time to charge and the potential to offer higher efficiencies compared to an on-board charger (Genovese et al, 2015). LVDC distribution can be applied in the form of dedicated EV charging networks where cable costs can be reduced, utilisation rates of a centralised DC charger increased and the integration of DERs can be easily accommodated (Tabari and Yazdani, 2013;Smith K.A. et al, 2016).…”
Section: Level-2 Applications (120-400 V Dc )mentioning
confidence: 99%
“…With respect to EV charging, 'fast' off-board DC chargers are believed to offer the most practical public charging system based on time to charge and the potential to offer higher efficiencies compared to an on-board charger (Genovese et al, 2015). LVDC distribution can be applied in the form of dedicated EV charging networks where cable costs can be reduced, utilisation rates of a centralised DC charger increased and the integration of DERs can be easily accommodated (Tabari and Yazdani, 2013;Smith K.A. et al, 2016).…”
Section: Level-2 Applications (120-400 V Dc )mentioning
confidence: 99%
“…This system reduces costs and increases asset utilization compared to existing charging solutions. Practical applications include: phased infrastructure deployment for public parking areas, the conversion of existing street-lighting networks to integrated DC charging [25] and multi-plexing of existing rapid DC chargers with high demand [26].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it has been suggested that EV charging points can be integrated with the existing street lighting network, because the distribution characteristic of street lighting in the urban area is similar with the distribution characteristic of charging points. Therefore, the street lighting pole with EV charging system is presented [16]. Smith et al introduced the concept of a DC Lighting and Charging network to increase the power transfer capability of the lighting cables in order to enable charging of EVs at a higher energy efficiency than AC [16].…”
mentioning
confidence: 99%
“…Therefore, the street lighting pole with EV charging system is presented [16]. Smith et al introduced the concept of a DC Lighting and Charging network to increase the power transfer capability of the lighting cables in order to enable charging of EVs at a higher energy efficiency than AC [16]. In addition, BMW and Ubitricity company, respectively, have deployed a street-light charging solution [17,18], which contribute to a greener city.…”
mentioning
confidence: 99%